France : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
This Financial System Stability Assessment paper on France provides summary of an assessment of the financial system. Dominated by internationally active financial conglomerates, the French financial system has made important progress since the last financial stability assessment program (FSAP). In order to address a build-up of systemic risks, the authorities have proactively used macroprudential measures and public communication. The government is pursuing a strategy to prepare Paris as a key financial hub, including by promoting crypto-assets, fintech, green finance, and market entry. Banking and insurance business lines, and the corporate sector, carry important financial vulnerabilities that need close attention. The FSAP thus has recommended augmenting policy tools to contain vulnerabilities and continue to act pre-emptively if systemic risks intensify. In order to mitigate intensification of corporate-and potentially household-vulnerabilities, the FSAP proposed: active engagement with the European Central Bank on the possible use of bank-specific measures; considering fiscal measures to incentivize corporates to finance through equity rather than debt; and a sectoral systemic risk buffer.